Quantifying the Seismicity Parameters of A New Model of Seismic Source Zone for Aceh and Surrounding Areas - Juellyan, Juellyan; Setiawan*, Bambang; Muttaqin, Muttaqin; Saidi, Taufiq (Graduate School of Universitas Syiah Kuala, 2022)
Aceh is justified as one of the Indonesian provinces with a high level of seismicity. This high seismicity certainly has a severe negative impact on various aspects of human life in Aceh and the surrounding areas. Various types of efforts must be carried out to solve and mitigate the problem caused by any earthquake in Aceh and the surrounding areas. One aspect that can be carried out to minimize the hazards of seismic activity is the characterization of the source of the earthquake. This characterization can be used for various purposes for further seismic-related studies, including for studying seismic hazard analysis using the probabilistic seismic hazard analysis (PSHA) method. This research aims to determine the characteristics of the seismic source zones for Aceh and the surrounding areas. Based on the geological setting and seismicity catalog data of Aceh and the surrounding areas, a new model of seismic source zones was developed. This new model proposed that Aceh and the surrounding areas be divided into four zones, namely shallow background seismic source zones (divided into two source zones), two deep background seismic source zones, two megathrust source zones, and one fault zone, namely the Sumatra fault zone. The results of this study suggest that Zone I and Zone II of shallow background seismic source zones have a-values of 2.36 and 4.7, b-values of 0.545, and Mmax of 7.7 and 6.8. Deep background seismic source zone I has an a-value of 4.43 and a b-value of 0.9 with a maximum magnitude of 7 Mw. Meanwhile, deep background seismic source zone II has an a-value of 3.28 and a b-value of 0.755 with a maximum magnitude of 6.1 Mw. Megathrust seismic source zone I has an a-value of 3.53 and a b-value of 0.691 with a Mmax of 7.7 Mw. Meanwhile, the megathrust seismic source zone II has an a-value of 3.81 and a b-value of 0.702 with a Mmax of 7.1 Mw. Sumatra fault seismic source zone has an a-value of 2.88 and a b-value of 0.615 with a Mmax of 6.7 Mw.